"Making news in global India : media, publics, politics" - "Udupa, Sahana, 1977-" (Delhi, 2016)
In the decades following India's opening to foreign capital, the city of Bangalore emerged, quite unexpectedly, as the outsourcing hub for the global technology industry and the aspirational global city of liberalizing India. Through an ethnography of English and Kannada print news media in Bangalore, this ambitious and innovative new study reveals how the expanding private news culture played a critical role in shaping urban transformation in India, when the allegedly public profession of journalism became both an object and agent of global urbanization. Building on extensive fieldwork carried out with the Times of India group, the largest media house in India, between 2008 and 2012, Sahana Udupa argues that the class project of the 'global city' news discourse came into striking conflict with the cultural logics of regional language and caste practices. Advancing new theoretical concepts, Making News in Global India takes arguments in media scholarship beyond the dichotomy of public good and private accumulation.
Keywords: Social Science